Heretical Innovations from the Perspective of Traditional Muslim Scholars - Firdaus Khairi, Abdul Kadir; Fadzli, Adam; Rahimah, Embong (2016)
The term of innovation or heresy (bid’ah) was used by the Prophet Muhammad in describing the practices which are contradicted with the true Islamic teachings. The danger of its deviation from Islamic teaching was further emphasized by the companions and later became guidelines among Muslim society. This article examines several particular events such as extremism in worshipping God and congregational prayer during fasting month that occurred during the times of Prophet Muhammad and the companions that were regarded as the beginning of heretical innovations in the history of Muslim society. These events had provided extensive discussion and remarkable debate among later Muslim scholars pertaining the permissibility or formidability of such practices which have no basis either in the Qur‟an or the traditions of the Prophet. The writing of this article uses content analysis approach that refers to several authentic references from both classical and modern literatures. It is found that differentiation of views among Muslim scholars concerning the conformity of some Islamic practices related to faith, worship and custom which have weakened Muslim unity.